2010
DOI: 10.1186/1472-6963-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Patient's site of first access to health system influences length of delay for tuberculosis treatment in Tajikistan

Abstract: BackgroundTajikistan has the highest incidence rate of tuberculosis (TB) in Central Asia. Its health system still bears many features from Soviet times and is under-funded. Affordability is a major barrier to health care. Little is known about health care seeking of TB patients in post-Soviet countries and their delay until the start of TB therapy. The low estimated case detection rate in Tajikistan suggests major problems with access to care and consequently long delays are likely.MethodsThe study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
4
23
0
1
Order By: Relevance
“…The average number of visits made before commencing treatment after an initial visit to a non-NTP provider was higher because TB might not have been considered during the first visit to the informal providers, as a result; the patients might have been given inappropriate care which led to several other visits before reaching the appropriate health facility for TB care. However, median number of visits made irrespective of the source of care in this study were similar to what was found in South Africa [26], but less than what was found in Tajikistan and urban Zambia, where TB patients made on the average 4.8 and 6.7 visits respectively [27,28]. Additional strategies to shorten the interval between HCP visits in the diagnostic pathway may further reduce health system delay in our setting and improve TB control.…”
Section: Discussionsupporting
confidence: 80%
“…The average number of visits made before commencing treatment after an initial visit to a non-NTP provider was higher because TB might not have been considered during the first visit to the informal providers, as a result; the patients might have been given inappropriate care which led to several other visits before reaching the appropriate health facility for TB care. However, median number of visits made irrespective of the source of care in this study were similar to what was found in South Africa [26], but less than what was found in Tajikistan and urban Zambia, where TB patients made on the average 4.8 and 6.7 visits respectively [27,28]. Additional strategies to shorten the interval between HCP visits in the diagnostic pathway may further reduce health system delay in our setting and improve TB control.…”
Section: Discussionsupporting
confidence: 80%
“…However, the data showed a tendency only and should be interpreted with care. The long treatment delays experienced by migrants developing TB in Russia could have contributed to higher costs (Ayé et al. 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare access consisted of six domains: ‘primary care access’, 69, 15,20,2731 ‘specialty care access’, 8,30 ‘urgent care access’, 9,20 ‘spatial access’ (including geographic and transportation barriers), 8,11,14,15,27,29,31,32–37 ‘communication access between visits’, 9,21,22,27 and ‘cultural access’ (including familiarity with patient’s culture and language barriers). 27, 29 The five domains related to care coordination included: ‘longitudinal continuity’, 5,8,9,11,25,31,36,3842 ‘relational continuity’ (defined as patient developing trust and respect for provider over time), 10,11,23,25,29,36,3946 ‘informational continuity’ (all providers have access to comprehensive patient information), 5,1012,14,21–23,25,36,3846 ‘cross-boundary coordination’ (coordination across different health care settings or systems), 11,21,25,39,41,45 and ‘follow up coordination’ (coordination related to appointments, medications, testing, or procedures recommended by initial visit). 9,21,22 …”
Section: Resultsmentioning
confidence: 99%